Anti-Müllerian hormone trend after laparoscopic surgery in women with ovarian endometrioma. (May 2013) - Litta, Pietro; D'Agostino, Giulia; Conte, Lorena; Saccardi, Carlo; Cela, Vito; Angioni, Stefano; Plebani, Mario
Abstract Operative laparoscopy is the gold standard in the treatment of endometriotic ovarian cysts. Excisional surgery is the best technique to prevent recurrences and improve symptoms but it may result in ovarian reserve damage due to the removal of healthy ovarian cortex. The aim of this study was to investigate the extent of the ovarian reserve damage after stripping technique of unilateral endometriomas, by dosing the Anti-Müllerian Hormone (AMH). This prospective study was conducted at the Center of Minimally Invasive Pelvic Surgery of the Department of Health of Woman and Child, University of Padua, from October 2010 to June 2012. Twenty-five women underwent excision of monolateral endometriosis ovarian cyst by stripping without accessing a bipolar coagulation and performing an intracortical suture. The AMH serum levels were estimated in the early proliferative phase of the cycle, before surgery (time 0), 24 h after surgery (time 1), the first menstrual cycle after surgery (time 2) and the third menstrual cycle after surgery (time 3). We found a nonstatistically significant decreases in serum AMH levels after surgical excision of the cysts. Our results suggest that an appropriate surgical technique, without the use of the bipolar coagulation of ovarian border, does not determine a significant reduction of ovarian reserve.